History of biomechanical research at the Ilizarov Centre (to the 100th anniversary of Academician G.A. Ilizarov) - E. N. Shchurova; T. I. Dolganova; D. V. Dolganov; T. I. Menshchikova (Acta Biomedica Scientifica)
Background. Biomechanical studies of both the Ilizarov apparatus itself and the physiological system “apparatus – limb” occupy a significant place in the history of the formation and elaboration of the Ilizarov method, developed in the middle of the last century at the Kurgan Research Institute of Experimental Traumatology and Orthopaedics (nowadays – the world-famous Centre named after its creator). The analysis of the history of biomechanical research in the formation of Ilizarov method is not without interest.The aim. To analyze the history and stages of development of biomechanical research in order to substantiate the effectiveness of the Ilizarov method of transosseous osteosynthesis.Results. The national medical industry did not produce the appropriate equipment for biomechanical research in the early 1970s. That is why a group of engineers was included into the Laboratory of Clinical Physiology and Biomechanics (established in 1971) of the Ilizarov Centre, which created equipment for studying the processes in the tissues of the limbs and in the structure of the Ilizarov apparatus itself during its traction and compression impact on biological structures. The community of physicians, scientists and engineers made it possible to overcome a number of difficulties and problems. In their scientific publications and dissertations, the laboratory staff paid great attention to biomechanical research during transosseous osteosynthesis with the Ilizarov apparatus. At present, the staff of the Ilizarov Centre continues the traditions established by G.A. Ilizarov. For the first time in our country, a computer 3D video analysis of the kinematics and kinetics of orthopedic patients gait was introduced; it was supplemented with embedded software for the preparation of a clinical report of human gait biomechanics.Conclusions. The initial stage of the biomechanical research at the Ilizarov Centre included the creation of the research equipment. Subsequently, the biomechanical studies carried out by the staff of the Centre for almost half a century have shown an applied and functional result of the realization of general biological regularities of the Ilizarov’s discovery. At present, the biomechanical research continues at a higher level with the use of modern high-tech equipment.